2017
DOI: 10.1002/pon.4584
|View full text |Cite
|
Sign up to set email alerts
|

Costs of an ostomy self‐management training program for cancer survivors

Abstract: A WOCN-led group self-help ostomy survivorship intervention provided affordable, effective, care to cancer survivors with ostomies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…These studies reported on a range of intervention types, according to their different intervention focus, which could be classified into CRC surveillance programme, 31,32 education (colostomy education, 33–37 psychosexual education, 38 psychoeducation, 39,40 healthy lifestyle education 41 ), psychosocial support, 42,43 supportive expression, 44,45 cognitive behavioural stress management (CBSM), 46 supportive care, 47–50 physical activity (PA) and/or dietary, 51–58 and survivorship care plan (SCP) 59,60 interventions. Detailed definitions of the interventions included are described in Table S1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These studies reported on a range of intervention types, according to their different intervention focus, which could be classified into CRC surveillance programme, 31,32 education (colostomy education, 33–37 psychosexual education, 38 psychoeducation, 39,40 healthy lifestyle education 41 ), psychosocial support, 42,43 supportive expression, 44,45 cognitive behavioural stress management (CBSM), 46 supportive care, 47–50 physical activity (PA) and/or dietary, 51–58 and survivorship care plan (SCP) 59,60 interventions. Detailed definitions of the interventions included are described in Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…The studies that were included reported on various delivery formats, including face‐to‐face (one‐on‐one or in a group), 33–35,39–41,45,46,60 telephone, 36,38,42,48–50,56 web‐based, 58 and multiple combination with the following formats: face‐to‐face, telephone, home visit, home‐based, or web‐based 37,43,44,47,51–55,57,59 . These interventions were delivered by a range of health professionals, for example, nurse, therapist, doctor, oncologist, dietitian, psychologist, social worker, or trained research assistant.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations